Analysis of Floating Mooring Buoy as Platforms at Sea - Aco Wahyudi Efendi (Politeknik Ilmu Pelayaran Semarang, 2023)
Analysis of the buoyancy of this platform for use in mid-ocean land survey operations where this platform is loaded with the weight of the tools and workers on the platform. The purpose of this research is to describe the buoyancy of the mooring buoys. The research was conducted by calculating the capacity and weight of each material used and the buoyancy of the buoy to be used as a platform for land surveys in mid-ocean, the ability of seawater to shift the size of the pontoon to be used as a platform and calculate the load on the pontoon itself to obtain the buoyancy value of the pontoon. The ability of the strapping between the pontoon and the anchor was calculated to anticipate unstable pontoon motion and must have a stress capability that exceeds the stress experienced when the pontoon is hit by a wave. The tension in the chain is greatest force is assumed, namely the force of the ballast. When the earthworks pontoon capacity is used as mooring buoy by estimating the total weight of the earthworks pontoon capacity, it is still in a semi-floating condition, although under certain conditions it will drop to as much as 95% of the estimated buoyancy pressure capacity of the mourning buoy.